2023
DOI: 10.14687/jhs.v20i2.6339
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ attitudes towards cancer and affecting factors in Turkey: A descriptive study

Abstract: Aim:The aim of this study was to investigate the attitudes of nursing students towards cancer as well as affecting factors. Method:This descriptive study was conducted with 949 nursing students at two state universities in Turkey. The population of this study included 1st, 2nd, 3rd, and 4th year students in the  nursing programs in two universities in the academic year. In collecting data, “Demographic Information Form” and “Questionnaire for Measuring Attitudes Toward Cancer - Community Version” scales were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(27 reference statements)
0
0
0
Order By: Relevance
“…Moreover, students' reflections showed the effects of clinical education in this ward on professional role development and personal growth in undergraduate nursing students. The findings revealed that students had both positive and negative clinical education experiences in this ward (22). Nursing students may experience negative feelings and attitudes in caring for cancer patients.…”
Section: Discussionmentioning
confidence: 93%
“…Moreover, students' reflections showed the effects of clinical education in this ward on professional role development and personal growth in undergraduate nursing students. The findings revealed that students had both positive and negative clinical education experiences in this ward (22). Nursing students may experience negative feelings and attitudes in caring for cancer patients.…”
Section: Discussionmentioning
confidence: 93%